Freshwater fish of Enggano Island, Indonesia - Renny Kurnia Hadiaty; Sopian Sauri (Masyarakat Iktiologi Indonesia (Indonesian Ichthyological Society), 2017)
Enggano is an outer island of the archipelago country, Indonesia. A field survey of freshwater fish fauna conducted in Enggano island to get the information of the ichthyofauna of this island. The fish collected in 11 freshwaters. We got 457 fish specimens of 28 species in 11 families and three orders. One species, Stiphodon sp. suspected to be new to science and five species require further study to clarify their taxonomical status. All of the fish collected specimens deposited in 77 catalog numbers of Museum Zoologicum Bogoriense (MZB). The ichthyofauna of this island could be use as the basic data for the resource management of the Enggano island. Abstrak Pulau Enggano merupakan satu pulau terluar dari negara kepulauan, Indonesia. Survei ikan air tawar dilakukan di Pulau Enggano dengan tujuan untuk mendapatkan informasi iktiofauna yang ada di pulau ini. Koleksi sampel ikan dilakukan di 11 perairan tawar. Kami memperoleh 457 spesimen dari 28 spesies yang termasuk dalam 11 famili dan 3 ordo. Satu jenis diantaranya, Stiphodon sp. diduga merupakan jenis baru dan lima jenis lainnya perlu dikaji lebih lanjut untuk mengetahui status taksonominya. Semua spesimen hasil koleksi dideposit di Museum Zoologicum Bogoriense (MZB) dalam 77 nomor MZB. Diharapkan data iktiofauna pulau ini dapat digunakan sebagai dasar pertimbangan pemerintah daerah dalam pengelolaan sumber daya P. Enggano.